1977
DOI: 10.1115/1.3448745
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW—A Critical Review of Turbomachinery Noise

Abstract: The review is written from the point of view of an engineer wanting to understand, reduce, and predict noise from turbomachines. In consequence knowledge gained by theory and, in particular, experiment is emphasized rather than the details of theoretical treatments. Attention is drawn to the surprisingly small interaction between theory and experiment and to the small amount of application that the theories have received. In describing the theoretical models it is the validity or applicability of their assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Quantitatively, the MVB configuration outperformed the other configurations in providing a reduction of 5 dB in the second BPF harmonic. Looking at this occurrence, Bianchi et al [22] showed that, according to Magliozzi et al [25] and Cumpsty [2], the second BPF might also be evidence of inflow disturbances from the plenum that were capable of affecting the end-wall boundary layer and interaction with the blade's trailing edge turbulent wake. The authors achieved the larger noise reduction produced by the MVB configurations in the broadband, in a range from 1.5-10 kHz, where a significant drop of L w (A) spectrum took place.…”
Section: Acoustic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Quantitatively, the MVB configuration outperformed the other configurations in providing a reduction of 5 dB in the second BPF harmonic. Looking at this occurrence, Bianchi et al [22] showed that, according to Magliozzi et al [25] and Cumpsty [2], the second BPF might also be evidence of inflow disturbances from the plenum that were capable of affecting the end-wall boundary layer and interaction with the blade's trailing edge turbulent wake. The authors achieved the larger noise reduction produced by the MVB configurations in the broadband, in a range from 1.5-10 kHz, where a significant drop of L w (A) spectrum took place.…”
Section: Acoustic Performancementioning
confidence: 99%
“…In particular, Wright [1] and Cumpsty's [2] works have enhanced the understanding of axial-turbomachinery aeroacoustics. Cumpsty [2] concluded that, with the exception of the low-frequency range of high-speed machines, the mechanism that determines broadband noise in subsonic fans is the same as that in supersonic tip-speed fans and compressors. According to Wright [1], this is due to the prominence of rotor noise originating from turbulent boundary layers.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, several investigations have been carried out to study these phenomena, with some focusing on the noise generation mechanisms. Cumpsty (1977) and Neise (1976) studied the tonal pulse generation in the centrifugal machines, demonstrating that changing the impeller and cut-off geometry could reduce the blade passage frequency tones. In 1963, Embleton (1963) implemented several design changes in the impeller and cut-off, such as sloping the cut-off and impeller blades, and including slots in the impeller blades.…”
Section: Introductionmentioning
confidence: 99%
“…Cumpsty [9] and Neise [10] focused the attention on the tonal pulse generation, whereas Mongeau [11], Mongeau et al [12], Choi [13], Choi et al [14], and Bent [15] showed that the flow structure was associated with the dominant unsteadiness of the spectral content at the impeller discharge.…”
Section: Introductionmentioning
confidence: 99%